2012
DOI: 10.2466/05.23.25.pms.114.2.665-678
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Implicit and Explicit Practice in the Development of Decision Making in Volleyball Serving

Abstract: This experiment investigated the effect of explicit, implicit, and sequential learning (implicit-explicit) on the acquisition and retention of decision-making skill in volleyball. The participants were 60 female novices, ages 10 to 12 years. The experimental groups followed three different methods of training: (a) explicit practice for the development of declarative knowledge, (b) implicit practice for the development of the procedural knowledge, (c) sequential practice (implicit first and then explicit), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…The results of the study conducted by Maleki, Shafie, Nia, Zarghami, and Neisi, (2010) have shown that feedback with model observation and simultaneous provision of verbal instructions improved learning in the skill of handstand, while feedback without verbal instructions did not show results in skills learning. Recently, Lazarides and Gorozides (2012) defined that the simultaneous use of video with verbal feedback is superior in comparison to the traditional method in teaching serving in volleyball to children of the first grade of high school and Lola, Tzetzis and Zetou (2012), defined that the video observation model effected on implicit practice in the development of decision making in volleyball serving.…”
Section: Jpes ®mentioning
confidence: 99%
“…The results of the study conducted by Maleki, Shafie, Nia, Zarghami, and Neisi, (2010) have shown that feedback with model observation and simultaneous provision of verbal instructions improved learning in the skill of handstand, while feedback without verbal instructions did not show results in skills learning. Recently, Lazarides and Gorozides (2012) defined that the simultaneous use of video with verbal feedback is superior in comparison to the traditional method in teaching serving in volleyball to children of the first grade of high school and Lola, Tzetzis and Zetou (2012), defined that the video observation model effected on implicit practice in the development of decision making in volleyball serving.…”
Section: Jpes ®mentioning
confidence: 99%
“…Due to the constant changes of ball possessions and the impossibility of retaining the ball, the precision of movements is determinant for the adequate linking of the game actions, as well as to obtain the dominion of the game. In addition, good collective performance depends on each athlete's ability / capacity to control movements with proficiency and to make effective decisions about motor response 25 . The relationship between increased likelihood of being effective and decreased efficiency seems to be associated with the poor experience of most of athletes investigated, coupled with the need to quickly adjust to the ball's trajectory and make quick decisions.…”
Section: Discussionmentioning
confidence: 99%
“…More experienced volleyball players usually act based on the familiarity they perceive between the problem situation presented by the game and certain situations previously experienced in the sport, performing the action typically more adequate to solve the present problem 30 . In this way, coaches need to balance explicit and implicit instruction strategies 25 , offering many problem situations in which players try to make decisions to discover solutions, as well as qualified guidelines regarding possible motor responses to the problems presented. Thus, the adoption of systematic training strategies for reflection and decision-making is suggested from the initial stages of volleyball training, considering its potential for the positive development of athletes in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Lola et al [66], players experienced a four-week intervention designed to improve decision-making related to the serve in volleyball. The intervention involved a program applied 3 times a week (12 practice sessions).…”
Section: Study Characteristicsmentioning
confidence: 99%